Value Added Analysis in Small Rice Milling Industry in Kabangka District, Muna Regency - Nirma Sulastri; La Rianda; Sakir Sakir (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2021)
The purpose of this study was to determine the added value obtained by the owner of a small rice milling industry in Kabangka District, Muna Regency. The data is processed using quantitative data to assess the added value in the rice milling industry. Data was collected by the following methods: (a) interviews, (b) library methods, and (c) documentation. This study uses the Hayami Method analysis. The number of respondents in this study was four people. The results showed that the owner of the rice milling business in one day made two productions. The number of raw materials in the two production processes was 1,150 kg per day. Hence, the total raw materials used by the rice milling business in one month was 34,500. by producing rice in one production of 750 kg per day. The whole rice produced by the rice mill in one month is 22,500 kg. The results showed that the milling business owner got an added value of Rp. 1,415 per Kg of raw materials, with a value-added ratio of 23%.